PENGARUH SUBTITUSI TEPUN GGEMBILI (Dioscorea esculenta) TERHADAP KARAKTERISTIK COOKIES: The Effect of Ggembili Flour Substitution (Dioscorea Esculenta) on Cookies Characteristics - Rifqi Mufarrochah Wardani; Arfiati Ulfa Utami; Rosiana Ulfa (JURNAL TEKNOLOGI PANGAN DAN ILMU PERTANIAN (JIPANG), 2023)
Wheat is one of the ingredients of food products that must be imported from other countries. Efforts to reduce dependence on wheat flour from other countries are by finding non-wheat flour auxiliary materials as food-making ingredients. One option is to utilize local tubers such as gembili. Gembili contains fiber and bioactive compounds, so it can be made into gembili flour and can be applied to food products that are popular with both children and adults, namely cookies. This study aimed to determine the effect of gembili (Dioscorea esculenta) flour substitution on the quality of cookies. The method used in this study was a completely randomized design (CRD). Research data shows that making cookies using gembili flour with different comparisons has the highest hedonic test value at P2 with a ratio of wheat flour and gembili flour (100:50) in the parameters of taste, aroma, texture, and color, with an average value of 3.54. 3.42, 3.69, and 3.31. The results of the water content test showed that making cookies with different comparisons of gembili flour had the lowest value, namely 1.21 at P5 with a ratio of wheat flour and gembili flour (0:150). The results of the test for crude fiber content had the lowest value, namely 0.56 at P1 with a ratio of wheat flour and gembili flour (150:0).